Interfaith Marriage in Bangladesh: A Theological and Sociological Study of Challenges, Barriers, and Backlash - Nazrul Islam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
This study explores the challenges faced by interfaith couples in Bangladesh, focusing on legal, cultural, and psychological barriers. It examines the impact of religious doctrines, legal frameworks, and societal norms on these unions. Drawing on socio-anthropological theories of religious pluralism and personal law, this research investigates how religious identity and legal structures intersect to shape the experiences of interfaith couples in Bangladesh. While interfaith marriage has been studied in various contexts, little attention has been paid to Bangladesh’s specific legal and religious landscape. Existing research points to significant legal barriers and social stigma, particularly for women, but lacks an integrated approach to the theological and institutional dimensions of these challenges. Using a qualitative research design, the study employs in-depth interviews, case studies, and document analysis. Participants included interfaith couples, religious scholars, and legal experts. Data were analyzed thematically to uncover key challenges and societal responses. The study finds that interfaith couples face doctrinal conflict, religious opposition, legal barriers, familial rejection, and societal exclusion. The Special Marriage Act (1872) is underutilized, and religious biases in legal systems exacerbate these challenges. Women are disproportionately affected, facing psychological distress, economic instability, and legal insecurity. The research highlights the need for a Uniform Civil Code and broader societal sensitization to promote legal protections, reduce stigma, and ensure equal rights for interfaith couples. This study offers a unique theological and sociological analysis of interfaith marriage in Bangladesh, contributing new insights into legal reform and social inclusion.